Latin American Consensus on management of residual cardiometabolic risk. A consensus paper prepared by the Latin American Academy for the Study of Lipids and Cardiometabolic Risk (ALALIP) endorsed by the Inter-American Society of Cardiology (IASC), the International Atherosclerosis Society (IAS), and the Pan-American College of Endothelium (PACE) (2022)
Digital